Sustaining Relationships Between Diaspora and Homeland: the Case of Singapore Hadhramis - Ameen Talib (International Journal Labs, 2023)
This paper deals with the Hadhrami diaspora in Singapore as a case study of how in contemporary events the Hadhrami diaspora has helped sustain the relationship with the motherland. What makes the study of Singapore Hadhramis interesting is that this is a community that has been in Singapore for over two centuries The other interesting aspect is that most families have migrated to Singapore via Indonesia and to a large extent consider themselves as Arab Jawa/Arab Indon. They have maintained close ties with Indonesia; in a sense Indonesia is the second motherland. The other element is that most migrated to Singapore with wealth made elsewhere; mainly from Indonesia. The fourth element is Singapore is a rich and developed country and most of the community do not harbour thoughts of returning to motherland but at same time are not severing ties. The last and most interesting element is that the majority of Singapore Hadhramis do not speak Arabic and have never visited Hadramaut. All these elements could have contributed to the Singapore Hadhrami community not maintain links with motherland. However strong bonds exist and continue. The pioneers, understandably, never forgot their motherland. They created numerous wakafs for Hadramaut.